Ora et non Labora? A Test of the Impact of Religion on Female Labor Supply - Francesco Pastore; Simona Tenaglia (Institute for the Study of Labor (IZA), 2013)
This paper examines the influence of religion on female participation to the labor market using data relative to women aged between 18 and 60 years in 47 European countries drawn from the European Values Study (EVS). We investigate the determinants of the probability of being employed rather than jobless in a LOGIT framework. The results show that women belonging to the Orthodox and, even more, Muslim denominations present a higher risk of non-employment than the agnostics, while being a Protestant increases the probability for a woman to be employed. Although its intensity is slightly weakening, the association between religious affiliation and female labor supply is robust to different sets of controls for individual and household heterogeneity as well as for welfare regimes and country specificities. Once disentangling religiously active and non-active women, we find that there are small differences between them in the case of the Orthodox and Muslim women, while active Catholic women tend to work less and non-active Protestant women tend to work more than average.
Keywords: D1; H75; J13; J16; J22; N30; Z12; 330; female labor supply; religion; welfare state regimes; child care